“Full Circle”: Theories of Property Rights as Indicated by Two Case Summaries Concerning the Individualization of Collective Indigenous Lands Interests - Tough, Frank J. (Journal of Aboriginal Economic Development, 2013)
The "Rule of Law" and "Individual Property Rights" are often regarded as necessary conditions for economic growth and development. Recently, the common ownership of First Nation reserve lands in Canada was identified as "Dead capital." Apparently, the problems of delayed development can be traced to a dysfunctional property system. A serious critique of collective ownership with its concomitant high transactions costs suggests a stronger on-reserve role for market relations. Only by individualizing land ownership and coming out from under the Indian Act can the commercial potential of reserve lands be realized. Clearly, a closer look at the property rights paradigm is required. To assist with a discussion of such proposals for development, this paper will employ a critical economic history approach, by (i) explaining the foundations of the property rights paradigm; (ii) employing two case summaries to demonstrate how US and Canadian authorities directed the conversion of collective Indigenous land holdings to individual transferable titles; and (iii) identifying some outcomes associated with the creation of transferable individual rights in property. Two case summaries demonstrate how economic history can illustrate the private property rights experiences of Indigenous peoples. Coercion by the United States government resulted in the breakup (allotment) and sale of large Indian territorial reservation lands. In the Canadian prairie west, Métis entitlements took the form of grants of millions of acres of scrip and the assignment or conveyance of their interests left them without a land base. In these cases, lands and entitlements ostensibly reserved for Indigenous peoples were diverted to emerging settler land markets. Evidence suggests that the weaker property rights of speculators/settlers triumphed over the legally recognized rights of Indigenous peoples. In other words, the Rule of Law in respect of property was somewhat different for settlers/speculators and Indigenous peoples. In these historical cases, the individualization of collective ownership into transferable assets had similar outcomes that do not seem to accord with predictions that economic growth will ensue from the promotion of private property rights and the reduced transaction costs.